ADPglucose pyrophosphorylase's N-terminus: Structural role in allosteric regulation - Bejar, C.M. (2006)
We studied the functional role of the Escherichia coli ADPglucose pyrophosphorylase's N-terminus in allosteric regulation, and the particular effects caused by its length. Small truncated mutants were designed, and those lacking up to 15-residues were active and highly purified for further kinetic analyses. NΔ3 and NΔ7 did not change the kinetic parameters with respect to the wild-type. NΔ11 and NΔ15 enzymes were insensitive to allosteric regulation and highly active in the absence of the activator. Co-expression of two polypeptides corresponding to the N- and C-termini generated an enzyme with activation properties lower than those of the wild-type [C.M. Bejar, M.A. Ballicora, D.F. Gómez Casati, A.A. Iglesias, J. Preiss, The ADPglucose pyrophosphorylase from Escherichia coli comprises two tightly bound distinct domains, FEBS Lett. 573 (2004) 99-104]. Here, we characterized a NΔ15 co-expression mutant, in which the allosteric regulation was restored to wild-type levels. Unusual allosteric effects caused by either an N-terminal truncation or co-expression of individual domains may respond to structural changes favoring an up-regulated or a down-regulated conformation rather than specific activator or inhibitor sites' disruption.